PENGARUH SERTIFIKASI GURU AGAMA TERHADAP PENGUASAAN MATERI PEMBELAJARAN SISWA DI MTs. NAHDHATUL UMMAH KETAPANG LOR UJUNGPANGKAH GRESIK - Afifah, Afifah; Mashuri, Imam (Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2020)
This research contained the first formulation of the problem of how religious teacher certification in MTs. Nahdhatul Ummah Ketapang Lor Ujungpangkah Gresik, the second is how to master student learning material in MTs. Nahdhatul Ummah Ketapang Lor Ujungpangkah Gresik, the third is the influence of religious teacher certification on the mastery of student learning material in MTs. Nahdhatul Ummah Ketapang Lor Ujungpangkah Gresi, the last is how much influence the religious teacher has on the mastery of student learning material in MTs. Nahdhatul Ummah Ketapang Lor Ujung pangkah Gresik. This research has the first objective to determine the religious teacher's certification, the second is to know the mastery of student learning material, the third is to find out whether or not the influence of religious teacher certification on the mastery of student learning material and the last is to know how much influence the religious teacher certification on mastery student learning material in MTs. Nahdhatul Ummah Ketapang lor Ujungpangkah Gresik.